BENEVOLENCE, COMPETENCY, AND INTEGRITY: WHICH IS MORE INFLUENTIAL ON TRUST IN FRIENDSHIPS? - Firmansyah, Muhammad Reza; Amelia, Riski; Jamil, Rizky Amalia; Faturochman, Faturochman; Minza, Wenty Marina (Jurnal Psikologi, 2019)
Personal variables are often assumed to affect trust. In Indonesia, there are three personal variables that affect trust: benevolence, competence, and integrity. This study aims to examine the influence of these three variables on friendship relationships. The respondents of this study consists of 220 students of Universitas Gadjah Mada (44.1% male and 55.9% female). Data were collected using the Trust Scale (Î± = .74), the Benevolence Scale (Î± = .85), the Competence Scale (Î± = .80), and the Integrity Scale (Î± = .78). Regression analysis revealed that competence has no significant influence towards trust, and the role of benevolence is greater than integrity. Based on these findings we constructed regression models with benevolence as the main variable and integrity as an additional variable. As a single factor, the contribution of benevolence is 21.4%. The addition of integrity in the regression model finds that the contribution of both variables together is 29.2%.